Evaluation method of sustainable development of plateau lakeside cities under the perspective of new development philosophy and its empirical research - Luo, Yi; Jia, Tingfang; Li, Anlin; Yang, Kun; Pei, Xingfang; Peng, Changqing; Chen, Rixiang; Li, Dingpu; Wang, Qingqing (Frontiers in Ecology and Evolution, 2023)
Sustainable Development Goals (SDGs) is another binding target indicator system proposed by the United Nations after the Millennium Development Goals (MDGs). Scientific monitoring of the state of sustainable development of cities can provide a reference for the progress of the implementation of the SDGs, and also provide research support for the successful achievement of the sustainable development of cities around the world. Although the indicator system proposed by the United Nations has drawn a vision of global sustainable development and given an evaluation framework and methodology, it fails to and is unlikely to encompass the rich connotations of China's new development philosophy. Therefore, this study takes the new development philosophy as the fundamental guideline, refers to the SDGs assessment system, and constructs a theoretical and methodological framework for assessing the sustainable development of plateau lakeside cities from the five dimensions of "innovation, coordination, greenness, openness, and sharing", and carries out empirical investigation in the research area of Kunming City, a typical plateau lakeside city. It is found that the sustainable development level of Kunming is at a medium level, with a relatively fast development speed, but the growth momentum has slowed down; the development level of each dimension is relatively low, with a slow development speed, showing a fluctuating upward trend; the change in the level of coordinated development shows two states of low and medium coordination, showing a steady increase; the contribution of the five philosophies of relevance is sorted as: "Openness>Sharing>Green>Coordination>Innovation", and openness is the most important factor affecting the sustainable development level of plateau lakeside cities.